Protonated heterocyclic derivatives of cyclopropane and cyclopropanone : classical species, alternate sites, and ring fragmentation - Miranda, Margarida S. (2015)
Fil: Miranda, Margarida S. Universidade do Porto. Faculdade de Ciências; Brazil.